Analisis Keterampilan Teknik Pukulan Backhand Bulutangkis pada Atlet Usia Remaja Klub Pelatkot Kota Gorontalo - Saromeng, Yusril; Pramono, Harry; Irawan, Fajar Awang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to find out and analyze the level of badminton technique skills at PB Pelatkot Gorotalo City in 2023. The method used in this research uses a quantitative approach with a survey research design to get a systematic, factual, and accurate picture of the facts and characteristics. The data collection technique was done by direct observation, simulating internal matches for Gorontalo Pelatkot athletes. The population and sample in this study were PB Pelatkot Gororntalo City athletes, totaling 20 athletes: 10 male athletes and ten female athletes. The sampling technique in this research was total sampling. This research shows the badminton hitting technique skills in PB Pelatkot Gorontalo athletes. Short serves have a success rate of 95.40% in the